Are they really motor learning therapies? A scoping review of evidence-based, task-focused models of upper limb therapy for children with unilateral cerebral palsy. Issue 9 (24th April 2023) - Taghizadeh, Atefeh; Webster, Kate E.; Bhopti, Anoo; Carey, Leeanne; Hoare, Brian
Abstract: Purpose: To identify the specific motor learning (ML) theories underpinning evidence-based, task-focused upper limb models of therapy for children with unilateral cerebral palsy; and to document the strategies used in the operationalisation of these theories. Material and Method: This scoping review searched for relevant studies using eight electronic databases. A list of 68 ML strategies and accompanying definitions was developed for data extraction. Three classifications; adequate, inadequate or not described were used to rate the description of ML strategies. A corresponding colour-coding system was used to provide a visual summary. Results: There is a limited description of the ML theories and strategies used to operationalise these theories in existing models of evidence-based upper limb therapy. Of 103 therapy protocols included, only 24 explicitly described the guiding ML theory. When described, there was significant variation in the underlying theories, leading to significantly different focus and content of therapy. Of the 68 ML strategies, only three were adequately described. Conclusions: To support treatment fidelity and the implementation of evidence-based, task-focused models of upper limb therapy in clinical practice, future research needs to provide explicit details about the underlying theories and strategies used in the operationalisation of these theories. Implications for rehabilitation: Evidence-based models of upper limb therapy purport to be based on motor learning theory, however, most provide a very limited description of the theories and strategies used. Dosage of practice is only one element that is specific to a therapy approach and other elements guided by the principles of type of task and type of feedback should be considered. To support the implementation of evidence-based approaches in clinical practice, and improve treatment fidelity, it is important for researchers to define the theories that guide therapy approaches and explicitly describe the strategies used to operationalise these theories.